Dossier Kant on Sentiments: Between Morality and Aesthetics Editors Faustino Fabbianelli and Antonino Falduto - Fabbianelli, Faustino; Antonino Falduto, (Con-Textos Kantianos. International Journal of Philosophy, 2025)
The concept of “sentiment” plays a fundamental role in the context of Kant’s philosophy, notwithstanding the clear centrality of reason in the transcendental enterprise. The dossier of the Journal Con-Textos Kantianosdedicated to the topic Kant on Sentiments: Between Morality and Aesthetics aims to make a genuine new contribution to the debate surrounding the renaissance of Kant studies in the last few decades dedicated to the “other” Kant, i.e. the one focusing on sensibility, sentiments and feelings. To this end, in the present dossier entitled “Kant on Sentiments: Between Morality and Aesthetics” we collected studies that focussed on the role played by the concept of sentiment both in the context of Kant’s philosophy overall and in the one of its legacy – from Kant’s time up to nowadays. A specific goal of the dossier is that of overcoming the gap of thinking of sentiments in a separate way, which does not consider the closeness of the ethical and aesthetic realms.